Leadership, Innovation and Entrepreneurship as Driving Forces of the Global Economy [electronic resource] : Proceedings of the 2016 International Conference on Leadership, Innovation and Entrepreneurship (ICLIE) - Benlamri, Rachid; Sparer, Michael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This volume aims to outline the fundamental principles behind leadership, innovation and entrepreneurship and show how the interrelations between them promote business and trade practices in the global economy. Derived from the 2016 International Conference on Leadership, Innovation, and Entrepreneurship (ICLIE), this volume showcases original papers presenting current research, discoveries and innovations across disciplines such as business, social sciences, engineering, health sciences and medicine. The pace of globalization is increasing at a rapid rate and is primarily driven by increasing volume of trade, accelerating pace of competition among nations, freer flows of capital and increased level of cooperation among trading partners. Leadership, innovation, and entrepreneurship are key driving forces in enhancing this phenomenon and are among the major catalysts for contemporary businesses trading in the global economy. This conference and the enclosed papers provides a platform in which to disseminate and exchange ideas to promote a better understanding of current issues and solutions to challenges in the globalized economy in relation to the fields of entrepreneurship, business and economics, technology management, and Islamic finance and management. Thus, the theories, research, innovations, methods and practices presented in this book will be of use to researchers, practitioners, student and policy makers across the globe.
Part I Technology, Innovations and Sustainability -- Modelling Technology Transfer in Green IT with Multi Agent System -- Application Offloading using Data Aggregation in Mobile Cloud Computing Environment -- Living Lab (LILA): An Innovative Paradigm for Community Development: Project of'XploR' Cane for the Blind -- Regenerator Losses in a Free Piston Stirling Engine -- Adopting Business Analytics to Leverage Enterprise Data Assets -- Enterprise Architecture for Innovation Realization and Sustainability -- Developing Medical Record for Follow-up of Wet Age-related Macular Degeneration -- Mobile Computing in the Construction Industry -- Mapping Business Aligned IT Perspective Patterns -- An Approach towards Assessing Effective IT Governance Setting -- Implementing a Mass Customization Business Model in the Health Industry -- Genetic Algorithms Systems for Wind Turbine Management -- Qualitative and Quantitative Study on Videotaped Data for Fire Emergency Response -- Albot: Do Virtual Words Strengthen the Credibility of Artificially Intelligent bots? -- Implementation of Hybrid Artificial Intelligence Techniques to Detect Covert Channels Attack in New Generation Internet Protocol IPv6 -- What is and How to Develop Sustainable Innovation? -- A Conceptual Model for the Relationship between Aligned Innovations and Sustainable Development for Project Based Organizations -- Project Manager Roles in Software Information Systems -- Divided We Fall -- Embracing Off-grid Communities in Rural Bangladesh to Promote Sustainable Living -- The Role of Organisational Commitment, Leadership Style, Strategic Human Resources Practices and Job Satisfaction Towards Sustainable Tourism Industry -- The Role of Leaders on Creating Creative Climate the Stimulates Creativity and Innovation in the Workplace -- Building Responsible Leaders in Universities -- On the Analysis of Cyber Physical Systems -- Innovation Marketing in the Health Industry -- Effective Power Saving Techniques on the Quality of VolP -- Cultural Business Intelligence Management -- Is the Avalanche of e-Learning Coming to the UAE? -- Facilitating Conditions and Cost in Determining M-commerce Acceptance in Jordan -- Auditing and Comparing Innovation Management Capability in the Municipal Field -- Sustainable Development of Rural Communities in Bangladesh by Integrating Mobile Internet and Agent Banking Technology -- Part II Contemporary Leadership and Management -- Clustering Countries According to their Cultural Proximity and Similarity -- Human Resources Management Skills Needed by Organizations -- A Case for Strategic Management in Higher Education in India -- The Effect of International Accounting Standards on Management Behavior -- Intercultural Competencies for Career Advancement -- Managerial Recruitment Issue in China -- Human Resources Management Practices -- Knowledge Management Practices in Saudi Arabian Public Sector Organizations -- Leadership Types in the Middle Eastern Context -- Women on Corporation Boards -- The Effects of Age on Job Crafting -- A Simulative Comparison of Output Commercial Value, Employment and Pollution Levels between a Chemical Cluster and a Standalone Aluminium Smelting Plant -- Is Spiritual Tourism an Innovation in Tourism for India and Pakistan? -- Business to Business Buyer-Seller Interactions -- Educational Tourism in Dubai -- Principals' Creative Leadership Practices and School Effectiveness -- Part III International Entrepreneurship and Small Business -- Family Entrepreneurial Teams Under the TPB Lens -- The Government's Role in the Importance of Entrepreneurship Education Amongst University Students in Malaysia -- Motivation Voices and Visions of Women Entrepreneurs in the UAE -- Weathering the Storm -- Work Motivation in Temporary Organizations -- Demand and Supply Firms' Interlock -- A Web-based Benchmarking Tool and Database for SME -- Analysis of Startup Ecosystems in Germany and in the USA -- Zero Debt Startup in Capital-Intensive Solar Industry -- Personal Trait and Innovation Performance in Micro and Small Enterprises -- Development Prospects for Franchising in Southeast Asia -- Entrepreneurship Education in UKM -- The Relationship between Conflict Management and Job Performance -- Part IV New Trends in Global Economics, Finance, and Management -- Volatility Persistence and Shock Absorption Capacity of the Malaysian Stock Market -- Augmented Reality -- Business Cycle Forecasts and Future Volatility -- Relationship between Working Capital Management and Profitability -- Information Systems Strategies to Reduce Financial Corruption -- Cross Market Price Mechanism between the US Copper Futures Market and a Newly Proposed Chinese Dollar Index -- The Assessment of the Global Financial Crisis on Dubai Financial Market Performance -- Internal Rate of Return IRR -- Quantitative Risk Analysis for International Project Management and Programs in an Emerging Economy -- Part V Islamic Banking and Finance -- Musharakah Financing as Addressed in IFSB Standard -- Performance Measurement of KMI 30 and KSE 30 Index in Karachi Stock Exchange -- The Challenges and Opportunities of Islamic Banking in Lebanon.
Keywords: Business; Entrepreneurship; Leadership